Transitioning Long-Acting Products to a Generic Marketplace: What's Missing?. (21st November 2022) - Brown Ripin, David H; Catlin, Kelly; Lewis, Linda; Resar, Danielle; Amole, Carolyn; Bollinger, Robert C; Flexner, Charles
Abstract: Development of and increased access to generic oral medications to treat high-burden diseases including human immunodeficiency virus (HIV), tuberculosis, viral hepatitis, and malaria have had a major impact on reducing global morbidity and mortality. However, access and adherence to these life-saving treatments remains limited for some of the most vulnerable and underserved populations, for whom stigma, control, and discretion are critical to decisions around care. Current efforts to develop long-acting formulations to treat and prevent these conditions could overcome many of these barriers. However, generic manufacturing of these innovative products will be required to ensure affordable access to the communities and patients in greatest need. Strategic investments in new infrastructure will be required even before markets and manufacturing costs are clear, to ensure that access to these new products is not delayed, particularly for patients in low- and middle-income countries. Unlike conventional oral medications, long-acting products require greater investment for formulation, packaging, and delivery. The requirement for long-term bioequivalence studies will introduce additional delays in regulatory approval of generic long-acting products, and expedited approval pathways must be developed. Lessons learned from the development of long-acting hormonal contraceptives and long-acting antiretroviral products may provide a way forward. Abstract : Long-acting (LA) drugs and formulations for infectious diseases need to be available in low- and middle-income countries in less expensive generic formats. Although the manufacture of LA products is more expensive than oral alternatives, there is precedent to allow their inexpensive production in a generic marketplace.